2020
DOI: 10.1038/s41389-020-00285-9
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide targets super-enhancer networks in pancreatic cancer cells and cancer-associated fibroblasts

Abstract: The tumor microenvironment in pancreatic ductal adenocarcinoma (PDAC) is highly heterogeneous, fibrotic, and hypovascular, marked by extensive desmoplasia and maintained by the tumor cells, cancer-associated fibroblasts (CAFs) and other stromal cells. There is an urgent need to identify and develop treatment strategies that not only target the tumor cells but can also modulate the stromal cells. A growing number of studies implicate the role of regulatory DNA elements called super-enhancers (SE) in maintaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 56 publications
(75 reference statements)
3
32
1
Order By: Relevance
“…Hyperactive transcription of c-myc is driven by super-enhancer in human cancers [ 55 57 ]. A recent study demonstrated that TPL disrupts super-enhancers in pancreatic cancer cells [ 58 ]. The levels of c-myc protein were decreased to undetectable level after TPL treatment for 24 h. This powerful inhibitory effect is a comprehensive result from simultaneously repression protein stability and transcription of c-myc by TPL.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactive transcription of c-myc is driven by super-enhancer in human cancers [ 55 57 ]. A recent study demonstrated that TPL disrupts super-enhancers in pancreatic cancer cells [ 58 ]. The levels of c-myc protein were decreased to undetectable level after TPL treatment for 24 h. This powerful inhibitory effect is a comprehensive result from simultaneously repression protein stability and transcription of c-myc by TPL.…”
Section: Discussionmentioning
confidence: 99%
“…Triptolide has obvious inhibitory effects on pancreatic cancer. Triptolide, as a super-enhancer (SE) interacting agent, may exhibit its antitumor activity by interfering with cell cross-talk and signal transduction in pancreatic ductal adenocarcinoma 41 .…”
Section: Biological Functionsmentioning
confidence: 99%
“…BRD4 is widely expressed in human tissues, cancer cells, 13 , 21 cancer-associated fibroblasts, 22 and chronic inflammatory fibroblasts (e.g., liver, 23 lung, 24 cardiovascular, 25 and renal 26 ). In fact, BRD4 is considered the dominant transcriptional regulator within the BET protein family, 27 and it plays a significant role in the onset and progression of malignant human diseases, especially by controlling tumor cell proliferation and apoptosis, making it the most studied BET protein in cancer therapy.…”
Section: Brd4: the Most Studied Bet Proteinmentioning
confidence: 99%